SOME WAYS TO TEACH YOUNG STUDENTS TO SPEAK A FOREIGN LANGUAGE (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Current article is devoted to the problems of teaching young kids foreign language. We do our best to analyze and give our recommendations. We consider the most important and urgent point is to take into account the age, interests and other specific features of learners. Teaching young learners different from pre-intermediate and intermediate learners classes.